Interpreters and the Writing of History in China - Lung, Rachel (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractThis article argues that interpreters are crucial figures in the recording of history. Evidence taken from historical texts in ancient China is used to verify the claim that interpreters’ notes might have been used as a reference in composing historical records. By documenting the Tang dynasty (AD 618-907) policy to have interpreters interview foreign envoys and submit the relevant accounts to the Bureau of Historiography, this article provides background for the link between interpreters’ interview notes and history compilation in China. Evidence is further drawn from the history of the Sui dynasty (AD 581-618), whereby an interpreter’s mediated account of the emperor’s conversation with a Japanese envoy was directly adapted. Most interestingly, pictorial and written documents of foreign peoples made in the mid-6th century during the Liang dynasty (AD 502-557) were found to be very similar to the written accounts about these foreign peoples in Liangshu, the history of the Liang dynasty, completed in the early 7th century. Apparently, there is a solid link between the interview accounts and historical accounts about foreign peoples in China. Thus, there is a strong possibility that interpreters’ notes, in the form of reports, provide important, if not primary, sources for history compilation in China.